2016
DOI: 10.1111/1475-6765.12160
|View full text |Cite
|
Sign up to set email alerts
|

Parenthood and the polarisation of political attitudes in Europe

Abstract: Abstract. Becoming a parent can affect the lives of men and women by introducing salient new social roles and identities, altered social networks and tighter constraints on financial resources and time. Even though modern family life has evolved in many important respects, parenthood continues to shape the lives of men and women in very different ways. Given that parenthood can change the lives of men and women in profoundly different ways, it seems that it would bring about changes in the way women and men th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 43 publications
1
32
0
2
Order By: Relevance
“…While parenthood has no effect on attitudes among women towards gay marriage, fathers are notably more conservative on the issue compared to non-fathers (Elder and Greene 2012). Recent work from Banducci et al (2016), based on data from the European Social Survey, similarly finds that parenthood can have a polarizing effect on attitudes among men and women. The strongest indication of this was found in countries where there is less state-subsidized support for parental responsibilities, emphasizing the importance of understanding the politics of pregnancy in different contexts.…”
Section: Previous Research and Hypothesesmentioning
confidence: 95%
“…While parenthood has no effect on attitudes among women towards gay marriage, fathers are notably more conservative on the issue compared to non-fathers (Elder and Greene 2012). Recent work from Banducci et al (2016), based on data from the European Social Survey, similarly finds that parenthood can have a polarizing effect on attitudes among men and women. The strongest indication of this was found in countries where there is less state-subsidized support for parental responsibilities, emphasizing the importance of understanding the politics of pregnancy in different contexts.…”
Section: Previous Research and Hypothesesmentioning
confidence: 95%
“…Here, there is a relevant distinction between policy‐specific attitudes and more general attitudes. Policy attitudes include attitudes related to policies, e.g., spending preferences, government responsibility attribution, and support toward welfare state policies (Banducci, Elder, Greene, & Stevens, ; Barabas, ; Busemeyer & Neimanns, ; Gingrich & Ansell, ; Jordan, ; Soss & Keiser, ). Soss and Keiser (), for example, show that the generosity of public assistance programs shapes the direction of citizens’ demands on the welfare system.…”
Section: Outcomes and Mechanisms In Policy Feedback Studiesmentioning
confidence: 99%
“…Policy context has also been shown to affect the gender gap in attitudes. For example, the European countries with the lowest levels of support for parental responsibilities simultaneously display the largest gender polarization in policy preferences (Banducci et al, 2016). More importantly, other comparative research has shown that while the gender division of labour relates to differences in experiences of work–family conflict and attitudes towards gender roles, this is in turn moderated by family policy context (e.g.…”
Section: Introductionmentioning
confidence: 99%